Development of an outpatient data warehouse system for Uthai Hospital - Klaithong, Somchok (Journal of the Thai Medical Informatics Association, 2025)
The objective of this study is to develop a health data warehouse and outpatient service database for Uthai Hospital in Phra Nakhon Si Ayutthaya Province. The hospital had been facing issues with delayed data analysis, inaccurate data that did not reflect the real situation, and data that did not meet user requirements, all of which hindered health planning and problem-solving efforts. The study will collect data from Uthai Hospital's outpatient service database for the fiscal years 2020-2023. The development process is divided into three phases: the first phase involves collecting data and questions from administrators and users; the second phase involves designing the structure and necessary tables for the data warehouse; and the third phase focuses on developing data analysis displays, such as charts and tables, to verify the completeness and accuracy of the data. QlikView Desktop, a powerful tool for quickly and easily visualizing various data dimensions, was used in this process. The results of the development showed that the data warehouse system can fully display essential data with detailed insights, including trends in patient visits, medical expenses categorized by illness type, treatment rights, treatment departments, and ranked reports by diseases, departments, and service units. It also presents data dimensions such as time, gender, and disease groups. Moreover, the system can be further developed to present data in various formats based on user requirements, allowing analyzed data to be used in planning and solving public health issues in the local area. References ดอกแก้ว ตามเดช และณรงค์ ใจเที่ยง.(2565), “การพัฒนาระบบข้อมูลสารสนเทศด้านสุขภาพจังหวัด พะเยา”,วารสารสาธารณสุขและวิทยาศาสตร์สุขภาพ, ปีที่ 5,ฉบับที่ 1,78-92,มกราคม-เมษายน 2565 chilchil learning blogspot.(2559), “การพัฒนาคลัง ข้อมูล”,[ออนไลน์].ได้จาก:http://chilchil-learning.blog spot.com/ [สืบค้น 2 กรกฎาคม 2567] RSU-MOOC.(2560), “หลักการออกแบบคลังข้อมูลแบบ Star Schema และ Snowflake Schema”, [ออนไลน์]. ได้จาก: http://tiprayong.blogspot.com/2017/09/ blog-post_28.html [สืบค้น 2 กรกฎาคม 2567] กลยรตน ศรภทรพพธ. “คลังข้อมูลและระบบสนับสนุน การตัดสินใจส􀂷ำหรับการพัฒนาระบบสุขภาพใประเทศไทย”, จุฬาลงกรณ์มหาวิทยาลัย; 2562. NIDA Wisdom.(2560), “ระบบธุรกิจอัจฉริยะ (Business Intelligence) กับการจัดการ Big data”, [ออนไลน์]. ได้จาก: https://www.mbamagazine.net/index.php/ school/b-school/item/626-business intelligence-big-data [สืบค้น 2 กรกฎาคม 2567] Kvakusha.(2555), “ระบบธุรกิจเชิงวิเคราะห์ ระบบธุรกิจ อัจฉริยะคืออะไร ข้อดีข้อเสีย ของเทคโนโลยี”, [ออนไลน์]. ได้จาก:https://kvakusha.ru/th/analiticheskie sistemy-biznesa-chto-takoe-business-intelligence-plyusy-i.html [สืบค้น 2 กรกฎาคม 2567] สำนักงานปลัดกระทรวงสาธารณสุข.(2558), “บทที่ 6 ระบบสุขภาพของประเทศไทย”, [ออนไลน์]. ได้จาก:http:// wops.moph.go.th/ops/thp/thp/userfiles/7_%20lesson6. pdf [สืบค้น 2 กรกฎาคม 2567]